Is the association between sociodemographic variables and physical activity levels in adolescents mediated by social support and self-efficacy? - Luanna A. Cheng; Gerfeson Mendonça; Joana M.S. Lucena; Cassiano R. Rech; José C. Farias, Júnior (Elsevier, 2020)
Objective: Analyze whether the association between sociodemographic variables and physical activity levels is mediated by psychosocial factors. Methods: This is a cross-sectional epidemiological study of public and private high school students in João Pessoa, Paraíba state, Brazil. A total of 2540 adolescents (57.0% female) were analyzed (16.4 ± 1.2 years). Physical activity was estimated using a questionnaire, self-efficacy, and parents' and friends' social support by scales, all previously validated. Results: The association between sex and the physical activity level of adolescents was partially mediated by the social support of parents (β = 0.79; p < 0.001) and friends (β = 2.96; p < 0.001), and the association between age and physical activity level was partially mediated by parents' social support (β = 0.78; p < 0.001). The associations between sex and age and physical activity levels of adolescents were mediated by the social support of parents and friends. Conclusions: Differences in physical activity levels between adolescent females and males and between younger and older adolescents may be partially explained by differences in social support provided by parents and friends. Implementation strategies to increase the social support of parents and friends may help reduce the differences in physical activity levels between these subgroups of adolescents. Resumo: Objetivo: Analisar se a associação entre variáveis sociodemográficas e níveis de atividade física é mediada por fatores psicossociais. Métodos: Este é um estudo epidemiológico transversal com estudantes do ensino médio de escolas públicas e privadas de João Pessoa, Paraíba, Brasil. Foram analisados 2.540 adolescentes (57,0% do sexo feminino) (16,4 ± 1,2 anos). A atividade física foi estimada por meio de questionário, autoeficácia e apoio social dos pais e amigos através de escalas, todas previamente validadas. Resultados: A associação entre sexo e o nível de atividade física dos adolescentes foi parcialmente mediada pelo apoio social dos pais (β = 0,79; p < 0,001) e dos amigos (β = 2,96; p < 0,001), e a associação entre idade e nível de atividade física foi parcialmente mediada pelo apoio social dos pais (β = 0,78; p < 0,001). A associação entre sexo e idade e níveis de atividade física dos adolescentes foi mediada pelo apoio social de pais e amigos. Conclusões: As diferenças nos níveis de atividade física entre adolescentes do sexo feminino e masculino e entre adolescentes mais jovens e mais velhos podem ser parcialmente explicadas pelas diferenças no apoio social fornecido pelos pais e amigos. A implementação de estratégias para aumentar o apoio social de pais e amigos pode ajudar a reduzir as diferenças nos níveis de atividade física entre esses subgrupos de adolescentes. Keywords: Adolescence, Motor activity, Self-efficacy, Social support, Mediated effect, Palavras-chave: Adolescência, Atividade motora, Autoeficácia, Suporte social, Efeito mediado